Development of highly stable and low toxic cationic liposomes for gene therapy - Aranya Manosroi (2018)
Cationic liposomes with high stability and low cytotoxicity for gene therapy have been developed. Luciferase plasmid DNA (pLuc) was used as a model gene. The empty liposomes and niosomes were prepared by freeze dried empty liposomes (FDEL) method. The entrapment of pLuc in the liposomes was by reconstitution of the lyophilized dried vesicles with the plasmid solution. The morphology of the vesicles showing multilamellar structure was characterized by transmission electron microscope (TEM) and cryo-TEM. Cytotoxicity of the vesicular formulations was investigated on mouse melanoma cell lines (B16F10) by MTT assay. Cationic liposomes and niosomes containing the cationic lipid DDAB were less cytotoxic than other bilayer vesicular formulations. The pLuc entrapped in the cationic DPPC/Chol/DDAB liposomes (at 1:1:1 molar ratio) exhibited higher stability than other vesicular formulations and the pLuc in solution when stored at 4, 30 and 50°C for 8 weeks. The entrapment efficiency determined by gel electrophoresis and gel documentation of the pLuc in this liposomal formulation was 100%. Luciferase gene expression of pLuc-loaded in cationic liposomes (lipoplexes) in HeLa cell lines was evaluated from luciferase activity determined by a luminometer at 24 and 48 h incubation. Percentages of cell proliferation of the lipoplexes on HeLa cell line at 24 and 48 h incubation were evaluated by the WST-1 assay. When the amount of DPPC or cholesterol was increased in the lipoplexes, the higher amount of DDAB was needed to protect pLuc from enzymatic degradation. However, DPPC and cholesterol exceeded 33 and 50% mol, respectively gave no gene expression. The DPPC/Chol/DDAB (at 1:1:1 molar ratio) lipoplex has demonstrated moderately lower luciferase gene expression and low cytoxicity. This lipoplex with the DDAB/pLuc weight ratio of 14:1 was the most desirable formulation for gene therapy because of its high stability, high luciferase gene expression and low cytotoxicity. © ECV Editio Cantor Verlag.